Plasma membrane calcineurin B‐like calcium‐ion sensor proteins function in regulating primary root growth and nitrate uptake by affecting global phosphorylation patterns and microdomain protein distribution. Issue 4 (19th November 2020) - Chu, Liang‐Cui; Offenborn, Jan Niklas; Steinhorst, Leonie; Wu, Xu Na; Xi, Lin; Li, Zhi; Jacquot, Aurore; Lejay, Laurence; Kudla, Jörg; Schulze, Waltraud X.
Summary: The collective function of calcineurin B‐like (CBL) calcium ion (Ca 2+ ) sensors and CBL‐interacting protein kinases (CIPKs) in decoding plasma‐membrane‐initiated Ca 2+ signals to convey developmental and adaptive responses to fluctuating nitrate availability remained to be determined. Here, we generated a cbl ‐quintuple mutant in Arabidopsis thaliana devoid of these Ca 2+ sensors at the plasma membrane and performed comparative phenotyping, nitrate flux determination, phosphoproteome analyses, and studies of membrane domain protein distribution in response to low and high nitrate availability. We observed that CBL proteins exert multifaceted regulation of primary and lateral root growth and nitrate fluxes. Accordingly, we found that loss of plasma membrane Ca 2+ sensor function simultaneously affected protein phosphorylation of numerous membrane proteins, including several nitrate transporters, proton pumps, and aquaporins, as well as their distribution within plasma membrane microdomains, and identified a specific phosphorylation and domain distribution pattern during distinct phases of low and high nitrate responses. Collectively, these analyses reveal a central and coordinative function of CBL–CIPK‐mediated signaling in conveying plant adaptation to fluctuating nitrate availability and identify a crucial role of Ca 2+ signaling in regulating the composition and dynamics of plasma membrane microdomains.